Leukocyte as an Independent Predictor of Lower-Extremity Deep Venous Thrombosis in Elderly Patients With Primary Intracerebral Hemorrhage - Wang, Gang; Zhao, Wenjun; Zhao, Zhiyong; Wang, Dengfeng; Wang, Dong; Bai, Ruobing; Hou, Boru; Ren, Haijun (Frontiers in Neurology, 2022)
Objective: Due to the interaction of leukocytes with platelets and coagulation factors, they may in turn play a role in hemostasis or the formation of thrombi. This study aimed to investigate the association of leukocytosis on admission with an increased risk of acute lower-extremity deep venous thrombosis (LEDVT) in elderly patients with primary intracerebral hemorrhage (ICH). Methods: This was a single-center, retrospective observational study of consecutive patients presenting with spontaneous ICH aged 60 years or more at Lanzhou University Second Hospital from January 2017 through September 2021. Clinical data and demographic information were collected and analyzed. Univariate and multivariate analyses were conducted to identify independent risk factors of acute LEDVT. One-to-one matching was implemented to balance important patient characteristics by the groups' propensity score matching (PSM) analysis. Results: A total of 371 elderly patients with primary ICH fulfilled requirements for both inclusion and exclusion, of whom 33 (8.89%) experienced LEDVT. Leukocyte counts were statistically higher in the LEDVT group compared to the non-LEDVT group [12.89(8.80-14.61) ×109/L vs. 8.31(6.60-10.75) ×109/L, p<0.001]. Multivariable analysis demonstrated that leukocyte was a significant independent risk factor [odds ratios (OR) 1.152, 95% confidence interval (CI) 1.049-1.266, p=0.003] for LEDVT. The optimal cut-off value of leukocyte count calculated by the receiver operating characteristic (ROC) curve to predict LEDVT was 10.22×109/L (area under the curve:0.714, 95%CI 0.665-0.759; the sensitivity was 72.73%; the specificity was 71.01%) in elderly patients with primary ICH. After one-to-one PSM, compared to the matched non-LEDVT group, the matched LEDVT group had significantly higher leukocyte counts [12.44(8.60-14.40) ×109/L vs. 8.86(6.57-11.54) ×109/L, p=0.013]. Elevated leukocytes were the only independent predictors of LEDVT in elderly patients with primary ICH. Conclusions: Leukocyte at admission is an independent risk factor of LEDVT in elderly patients with primary ICH.